Market feasibility of faecal sludge and municipal solid waste-based compost as measured by farmers’ willingness-to-pay for product attributes: evidence from Kampala, Uganda - Danso, George K.; Otoo, Miriam; Ekere, W.; Ddungu, S.; Madurangi, Ganesha (MDPI, 2017)
There is a great potential to close the nutrient recycling loop, support a ‘circular economy’ and improve cost recovery within the waste sector and to create viable businesses via the conversion of waste to organic fertilizers. Successful commercialization of waste-based organic fertilizer businesses however largely depends on a sound market. We used a choice experiment to estimate farmers’ willingness-to-pay (WTP) for faecal sludge and municipal solid waste-based (FSM) compost in Kampala, Uganda and considered three attributes—fortification, pelletization and certification. Our results reveal that farmers are willing to pay for FSM compost and place a higher value on a ‘certified’ compost product. They are willing to pay US $0.4 per kg above the current market price for a similar certified product, which is 67 times higher than the cost of providing the attribute. Farmers are willing to pay US $0.127 per kg for ‘pelletized’ FSM compost, which is lower (0.57 times) than the cost of providing the attribute. On the other hand, farmers require US $0.089 per kg as a compensation to use ‘fortified’ FSM compost. We suggest that future FSM compost businesses focus on a ‘certified and pelletized’ FSM product as this product type has the highest production cost–WTP differential and for which future businesses can capture the highest percentage of the consumer surplus. The demand for FSM compost indicates the benefits that can accrue to farmers, businesses and the environment from the recycling of organic waste for agriculture.